Oral Health Status of Children Who Require In-Home Medical Care - França, Kamilla; Rezende Batista, Merielle; Fragelli, Camila Maria Bullio [UNESP]; Herval, Álex Moreira; Paranhos, Luiz Renato; Sabino-Silva, Robinson; Soares, Priscilla Barbosa Ferreira; Turrioni, Ana Paula (My University, 2021)
Purpose: To evaluate the oral health status of children who require in-home medical care, their oral hygiene and eating habits, and the association between oral health status and medical conditions.
Methods: Legal guardians of children who need in-home medical care were interviewed regarding their socioeconomic level and their children's medical and dental history, as well as their oral hygiene habits. An oral exam assessed the children's plaque level, caries experience, and periodontal disease. Descriptive and bivariate analyses were performed.
Results: Fifty-six children participated. Almost 61 percent had never received dental care and 58.9 percent had fair or poor oral hygiene. The most observed oral problems were gingival hyperplasia (46.4 percent), calculus (46.4 percent), and gingivitis (30.3 percent). The use of anticonvulsants and type of food were factors that correlated to calculus, gingivitis, or hyperplasia (P <0.05).
Conclusion: A significant number of children who require in-home medical care presented with deficient oral hygiene and periodontal problems, which were correlated with the use of anticonvulsants and gastrostomy feeding.